THE ANALYSIS OF LANGUAGE FEATURES ON NARRATIVE TEXT MADE BY SOCIAL TENTH GRADER AT SMAN 1 GROGOL KEDIRI - Nugraha, Luki Cahya (Jurnal Pendidikan Bahasa Inggris Proficiency, 2020)
The aim of this study was to describe the using of language features on narrative text and the language features appropriateness on narrative text and the problem that made social tenth grader cannot use language features appropriately. The researcher used descriptive qualitative approach as research design. The researcher collected the data by analyzing the student narrative’s language features, conducting interview with random students from five classes, and collecting document that supported this research. The data were collected from a Google form, interview script, and student’s narrative text regarding their writing experiences. The techniques of analyzing data were reduction the data, data analysis, presenting the data, and drawing conclusion. The result of this study showed that most of the social tenth grader were using language features on their narrative text such as Action verb, Time Sequence, Simple past tense, Descriptive language, and Specific Characters. But, none of their using Dialogue, Direct and Indirect speech on making narrative text. From Google form, the result showed that most of the student answered the question about narrative’s language features with the right respond. Then from interview, the result showed that the reason why the social tenth grader didn’t use language features on their narrative text was due to the ignorance about the features itself.